Diagnostic value of sST2, VCAM-1, and adiponectin in patients with breast cancer to predict anti-tumour treatment-related cardiac events: a pilot study - Rosenkaimer, Stephanie L.; Winter, Laura; Sieburg, Tina; Maier, Sandra; Mavratzas, Athanasios; Hofmann, Wolf-Karsten; Akın, Ibrahim; Dürschmied, Daniel; Hofheinz, Ralf-Dieter; Hohneck, Anna (Oncology research and treatment, 2022)
Aim: The present exploratory study investigated the diagnostic value of inflammatory markers in patients with breast cancer to predict anti-tumour treatment-related cardiac events. Methods: Twenty-one patients with breast cancer were enrolled in this prospective observational study and followed over 6 months. Transthoracic echocardiography and measurement of cardiac (N-terminal prohormone of brain natriuretic peptide (NT-proBNP), troponin I (TnI)) and inflammatory biomarkers (vascular adhesion molecule 1 (VCAM-1), soluble suppression of tumorigenesis-2 (sST2), adiponectin) was performed at 3-month intervals (baseline, follow-up, final visit). Cardiac events were defined as decrease in left ventricular ejection fraction (LVEF, decrease by 10% or <50%) or increase in global longitudinal strain (GLS, increase by 15% or > −16%), as a more sensitive marker of LV function. Results: Cardiac deterioration was observed in 9 out of 21 patients (event group). While LVEF did not differ significantly between the two groups (event vs. no event) at any visit, GLS was significantly higher during follow-up (follow-up: event −16 ± 3.3% vs. no event −18 ± 1.6%, p = 0.04; final visit: event −16 ± 2.1% vs. no event −19 ± 1.9%, p = 0.003). NT-proBNP was numerically higher in patients with a cardiac event during all visits, with NT-proBNP negatively correlated with LVEF and MAPSE (both r = −0.33, p = 0.02), whereas GLS (r = 0.40, p = 0.006), TnI (r = 0.44, p = 0.001), and VCAM-1 (r = 0.48, p = 0.003) showed a positive association with NT-proBNP. In comparison, higher VCAM-1 and sST2 concentrations were detected in the event group at both baseline and the final visit, with a significant difference for baseline (VCAM-1: p = 0.02; sST2: p = 0.03). Adiponectin was also lower in patients with a treatment-related event. Thresholds for VCAM-1 >762 ng/mL and sST2 >18.7 ng/mL, as detected by ROC analysis, correlated best with the primary endpoint. Conclusion: Cardiac events during anti-tumour treatment in patients with breast cancer are relatively common. Inflammatory markers such as VCAM-1 or sST2 were associated with an increased likelihood for occurrence of a treatment-related event, which may therefore hold the promise to better identify patients at high risk.
Online veröffentlicht: 28. June 2022
Gesehen am 30.09.2024